Optimal tax mix in a two-sector growth model with transitional dynamics - James B. Davies; Jie Zhang; Jinli Zeng (The University of Western Ontario, Department of Economics, 2000)
This paper examines the problem of optimal tax mix analytically in a two-sector growth model with transitional dynamics. Tax revenue is required to provide a pure public good. The key problems are: over-consumption of leisure under labor income or consumption taxes; and under-investment in human and physical capital under income taxes. Without investment subsidies, consumption taxes do better than uniform income taxes, but can be improved on locally via positive taxation of physical capital income and a negative tax on labor income. With subsidies the first best can be achieved in a system where: (i) consumption and labor income taxes are either zero or of the same rate but opposite signs; (ii) physical capital income taxes are used either exclusively or more heavily than labor income taxes when their rates are below 100%; and (iii) investment subsidy rates equal income tax rates for both forms of capital, respectively. In any given circumstances, a range of alternative tax mixes may provide equivalent results. This result, combined with practical constraints, may help to explain the variety of tax mixes observed across countries.
Keywords: E60; H20; O40; 330; growth; transitional dynamics; optimal taxation; subsidies; Optimale Besteuerung; Kapitalertragsteuer; Mehr-Sektoren-Modell; Neue Wachstumstheorie